2014
DOI: 10.1039/c3sm51990b
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of interactions between dendrimers and asymmetric membranes at different transport stages

Abstract: Studying dendrimer-biomembrane interactions is important for understanding drug and gene delivery. In this study, coarse-grained molecular dynamics simulations were performed to investigate the behaviors of polyamidoamine (PAMAM) dendrimers (G4 and G5) as they interacted with asymmetric membranes from different sides of the bilayer, thus mimicking different dendrimer transport stages. The G4 dendrimer could insert into the membrane during an equilibrated state, and the G5 dendrimer could induce pore formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Considering the similar levels of total cellular FITC-BC-PAMAM accumulation (Figure 8), the controlled transport of bioconjugated dendrimers into the nucleus might only proceed at nontoxic cellular dendrimer concentrations. At higher toxic concentrations, the direct interaction of cationic dendrimers with elements of the nuclear envelope may cause lipid membrane perforation as previously described 22,64,65 and concentration-dependent dendrimer entry into nucleus by simple diffusion.…”
mentioning
confidence: 68%
“…Considering the similar levels of total cellular FITC-BC-PAMAM accumulation (Figure 8), the controlled transport of bioconjugated dendrimers into the nucleus might only proceed at nontoxic cellular dendrimer concentrations. At higher toxic concentrations, the direct interaction of cationic dendrimers with elements of the nuclear envelope may cause lipid membrane perforation as previously described 22,64,65 and concentration-dependent dendrimer entry into nucleus by simple diffusion.…”
mentioning
confidence: 68%
“…The interactions between cationic G4 and G5 PAMAM dendrimers and asymmetric DPPC/DPPE/DPPS membranes have also been studied by He et al using CG simulations [126]. When the outer leaflet of the membrane contained 10% DPPS and the inner leaflet contained 50% DPPS, it was found that the G4 dendrimer inserted into the outer membrane and the G5 dendrimer caused pore formation.…”
Section: Coarse-grained Simulationsmentioning
confidence: 99%
“…[83, 8586] They have been reported to further improve the flux enhancement seen with small molecule CPEs such as isopropyl myristate. [80, 83] Although coarse-grained molecular dynamic simulation showed that larger dendrimers with generation numbers greater than four can penetrate biomembranes, [87] this has not been borne out experimentally. [8384, 88] Cationic dendrimers can disrupt the lipid bilayers by forming nanoscale pores.…”
Section: Transdermal Drug Deliverymentioning
confidence: 99%